Immunological protection against digoxin toxicity - Schmidt, Donald H. (1971)
The lethal dose of digoxin was determined by administering 10 ml of a digoxin-saline solution to 26 nonimmunized rabbits through an ear vein over a 10 min period. Rabbits receiving less than 0.45 mg/kg digoxin showed no toxic effect, whereas all 15 rabbits that received 0.5 mg/kg developed an early arrhythmia and died within 1 hr. Moreover, eight rabbits which had been immunized with antigens unrelated to digoxin or injected with Freund's adjuvant mixture all died after receiving 0.6 mg/kg digoxin. Thus, it was concluded that 0.6 mg/kg digoxin was uniformly lethal in rabbits that had not been immunized or had received antigens unrelated to digoxin. By way of contrast, 17 rabbits immunized with a digoxin-albumin conjugate in complete Freund's adjuvant formed digoxin-specific antibodies and survived doses of digoxin varying between 0.6 and 0.9 mg/kg. In 10 rabbits immunized with digoxin-albumin conjugates, digoxin-specific antibody titers were determined following the administration of digoxin. There was a significant fall in antibody titer. This study indicates that rabbits protected by digoxin-specific antibodies suffer no acute adverse effects from an amount of digoxin which is uniformly lethal in nonimmunized rabbits and in rabbits immunized with other antigens.